2021
DOI: 10.1007/s10334-020-00905-w
|View full text |Cite
|
Sign up to set email alerts
|

3D magnetization transfer (MT) for the visualization of cardiac free-running Purkinje fibers: an ex vivo proof of concept

Abstract: Objectives We investigate the possibility to exploit high-field MRI to acquire 3D images of Purkinje network which plays a crucial role in cardiac function. Since Purkinje fibers (PF) have a distinct cellular structure and are surrounded by connective tissue, we investigated conventional contrast mechanisms along with the magnetization transfer (MT) imaging technique to improve image contrast between ventricular structures of differing macromolecular content. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Eliav et al 43 and Kim et al 44 demonstrated that the collagen matrix greatly contributes to the MT; moreover, there was a linear correlation between the MTR ratio and percentage of collagen in vitro. It was recently shown that MTR varies in the heart as a function of the collagen type (I vs. III) 45 . Indeed, the relative proportion of type I and type III collagen is expected to evolve with age and pathologies in the cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Eliav et al 43 and Kim et al 44 demonstrated that the collagen matrix greatly contributes to the MT; moreover, there was a linear correlation between the MTR ratio and percentage of collagen in vitro. It was recently shown that MTR varies in the heart as a function of the collagen type (I vs. III) 45 . Indeed, the relative proportion of type I and type III collagen is expected to evolve with age and pathologies in the cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since MTI measures the MT between free water and water bound to macromolecules through chemical exchange and/or dipole-dipole interaction, it can Therefore, MTI can be used to more specifically detect how to organize the microstructure of collagen fibers, and how to reshape the extracellular matrix (92). Ho et al used freshly prepared amniotic eyes to evaluate the tissue magnetic resonance relaxation in response to dynamic IOP changes.…”
Section: Mtimentioning
confidence: 99%